IMPROVING STUDENTS’ SPEAKING ABILITY USING COOPERATIVE SCRIPT - Aseptiana Parmawati; Rasi Yugafiati (PROJECT (Professional Journal of English Education), 2022)
The ability to speak English is one of the benchmarks in determining success in education, especially for students majoring in English. Cooperative script is a method of learning in which students work in pairs and alternately convey orally explain the material. This research was conducted at IKIP Siliwangi. The subjects of the research were second semester students. Classroom Action Research was used in this research. Test and interview as the instrument of the research. The finding of the research proved that cooperative script can improve students’ speaking ability. It can seen from the improvement of the students score. The students mean score of pre-test was 71.60. After the implementation of cooperative script, the mean scores of post-test 1 was 74.40 And the mean scores of post-test 2 was 79.00. It means the result of this study confirm that the application of cooperative script can improved the student speaking ability. Keywords:  CAR, Speaking Ability, Cooperative Script